Commented translation of "On the Influence of Carbonic Acid in the Air upon the Temperature of the Ground" from Svante Arrhenius (1896) - Rasch, Matheus Barbosa; Lima, Maria Tereza Weitzel Dias Carneiro (Cadernos de Astronomia, 2025)
Published in 1896 in the Philosophical Magazine and Journal of Science, Arrhenius’ scientific paper is a pioneer in the quantitative study of the greenhouse effect, a central theme in the discussion on global warming. As well as being an important historical record, it is interesting to note that this work contains a methodology that paved the way for today’s climate models.